PENDAMPINGAN SISTEM INFORMASI POSYANDU TERINTEGRASI MENINGKATKAN EFIKASI DIRI - Rahman, La Ode Abd; Handiyani, Hanny; Chandra, Muhammad (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Self-efficacy is the belief in own abilities to be success in specific situation. Three dimensions of self-efficacy included magnitude, strength, and generality. Informational system of integrated service centre is an administrational system which could be used to accommodate and help the cadre in documenting of the integrated service centre activities. Aim of this study was to comprehend the difference of self-efficacy before and after integrated integrated service centre informational system supervision. This study design used One Groups Pretest-Posttest Design. Study population were Cadres of Flamboyant integrated service centre. Samples of the study were 8 respondents. Sampling technique used total sampling. Paired t-test used to comprehend the difference of self-efficacy before and after intervention. Study result showed that there was a difference of self-efficacy before and after integrated integrated service centre informational system assistance with mean pre-test and post-test was –4.06250, there was tend to increasing of knowledge before and after integrated integrated service centre informational system assistance. P-Value was 0.019, there was association between efficacy and supervision.Keywords: Service center informational system, Self-efficacy, supervision